The Effects of Neuronal Fyn Knockdown in the Hippocampus in the Rat Kainate Model of Temporal Lobe Epilepsy - Nikhil S. Rao; Marson Putra; Christina Meyer; Sirisha Parameswaran; Thimmasettappa Thippeswamy (Cells)
Previous studies have demonstrated neuronal and microglial Fyn, a Src family kinase (SFK), and how its interactions with tau contribute to epileptogenesis. Saracatinib, a Fyn/SFK inhibitor, modifies disease progression in rat kainate (KA) epilepsy models. In this study, we investigated neuronal-specific fyn knockdown effects on Fyn–tau signaling, neurodegeneration, and gliosis using a calcium/calmodulin-dependent protein kinase II (CaMKII)-promoter-driven adeno-associated viral vector (AAV9)-mediated fyn-shRNA injection in the rat hippocampus. Eight days following AAV administration, rats received repeated low-dose KA injections intraperitoneally to induce status epilepticus (SE). Both fyn-shRNA and control groups showed comparable SE severity, indicating inadequate neuronal fyn knockdown at this timepoint. Two weeks post fyn-shRNA injection, hippocampal Fyn significantly decreased, alongside reductions in NR2B, pNR2BY1472, PSD95, and total tau. There was also a compensatory activation of SFK (pSFKY416:Fyn) and tau hyperphosphorylation (AT8:total tau), negatively correlating with NeuN expression. Proximity ligation assay indicated unchanged Fyn–tau interactions, suggesting tau interactions with alternative SH3 domain proteins. Persistent neuronal loss, astrogliosis, and microgliosis suggested limited effectiveness of neuronal-specific fyn knockdown at this timepoint. An extended-duration fyn knockdown study, or using broad SFK inhibitors such as saracatinib or tau-SH3 blocking peptides, may effectively prevent SE-induced epileptogenesis.